Pelvic organ prolapse surgery after native tissue vault suspension at hysterectomy—A prospective cohort study. (September 2019) - Bonde, Lisbeth; Østergaard, Lauge; Fosbøl, Emil L.; Møller, Lars A.; Ottesen, Bent; Gislason, Gunnar H.; Gimbel, Helga
Abstract: Objective: The effect of prophylactic vaginal vault suspension during hysterectomy in prevention of subsequent development of pelvic organ prolapse (POP) is unknown. We aimed to investigate incidences and risk of POP surgery in women who had undergone hysterectomy on benign indication with and without prophylactic suspension. Study design: We linked the national clinical Danish Hysterectomy and Hysteroscopy Database (DHHD) to administrative registries to assess data on all total hysterectomies (1 May 2012 to 31 December 2014), suspension methods, age, POP surgery, births, obstetric complications, prescriptions, socioeconomic- and vital status. Women undergoing total hysterectomy on non-prolapse and benign indication with no prior POP surgery were included and followed from hysterectomy to POP surgery, death/emigration or end of study period (maximum 2 years). Descriptive statistics, cumulative incidence curves and multivariable Cox proportional hazard models were fitted to assess the associated risk of POP in relation to prophylactic suspension. Results: We included 7625 patients undergoing total hysterectomy; of these, 6538 (85.7%) were registered with prophylactic suspension during hysterectomy and 1087 (14.3%) women were specifically registered with no suspension in the DHHD. At baseline, women undergoing hysterectomy with suspension were on average 47.1 years of age (standard error SE 0.1) compared to 48.4 years (SE 0.3) in women with no suspension (p-value <0.0001). Moreover, women with suspension differed from their counterparts with no suspension with respect to geographical site of hysterectomy, hysterectomy method, parity and income. The cumulative risk of POP surgery after two years follow-up was 0.9% and 0.5% in the suspension group and the no suspension group, respectively. In the adjusted analysis, we found no association of prophylactic suspension and risk of POP surgery, hazard ratio (HR) = 2.1 (95% confidence interval (CI) 0.8–5.3, p-value 0.13). Conclusion: Of all women undergoing hysterectomy for benign indication, 0.84% (N = 64) were surgically treated for POP. At two-year follow-up, there was no association between prophylactic vaginal vault suspension at time of hysterectomy and subsequent POP surgery.